Global consensus building and prioritisation of fundamental lupus challenges: the ALPHA project. Issue 1 (19th July 2019) - Manzi, Susan; Raymond, Sandra; Tse, Karin; Peña, Yaritza; Anderson, Annick; Arntsen, Kathleen; Bae, Sang-Cheol; Bruce, Ian; Dörner, Thomas; Getz, Kenneth; Hanrahan, Leslie; Kao, Amy; et al.
Abstract : Objective: Lupus is a complex, heterogeneous autoimmune disease that has yet to see significant progress towards more timely diagnosis, improved treatment options for short-term and long-term outcomes, and appropriate access to care. The Addressing Lupus Pillars for Health Advancement (ALPHA) project is the first step in establishing global consensus and developing concrete strategies to address the challenges limiting progress. Methods: A Global Advisory Committee of 13 individuals guided the project and began barrier identification. Seventeen expert interviews were conducted to further characterise key barriers. Transcripts were analysed using Nvivo and a codebook was created containing a list of thematic 'nodes' (topics) and their descriptions. Findings were used to develop a final survey instrument that was fielded to a diverse, international stakeholder audience to achieve broad consensus. Results: Expert interviews identified lupus heterogeneity as the primary barrier hindering advancement. Subsequent barriers were categorised into three areas: (1) Drug development. (2) Clinical care. (3) Access and value. The global survey received 127 completed responses from experts across 20 countries. Respondents identified barriers as high priority including the lack of biomarkers for clinical and drug development use, flawed clinical trial design, lack of access to clinicians familiar with lupus, and obstacles to effective management of lupus due to social determinants of care. Respondents also identified 30 autoimmune conditions that may be lupus-related based on overlapping features, shared autoantibodies and pathophysiology. Conclusions: ALPHA is a comprehensive initiative to identify and prioritise the continuum of challenges facing people with lupus by engaging a global audience of lupus experts. It also explored views on lupus as a spectrum of related diseases. Conclusions from this effort provide a framework to generate actionable approaches to the identified high-priority barriers.